2016
DOI: 10.1002/anie.201609459
|View full text |Cite
|
Sign up to set email alerts
|

Controlling Singlet–Triplet Energy Splitting for Deep‐Blue Thermally Activated Delayed Fluorescence Emitters

Abstract: The development of efficient metal-free organic emitters with thermally activated delayed fluorescence (TADF) properties for deep-blue emission is still challenging. A new family of deep-blue TADF emitters based on a donor-acceptor architecture has been developed. The electronic interaction between donor and acceptor plays a key role in the TADF mechanism. Deep-blue OLEDs fabricated with these TADF emitters achieved high external quantum efficiencies over 19.2 % with CIE coordinates of (0.148, 0.098).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

9
280
0
3

Year Published

2018
2018
2020
2020

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 428 publications
(306 citation statements)
references
References 49 publications
9
280
0
3
Order By: Relevance
“…The Fc/Fc + redox couple was used as an internal standard to calibrate the oxidation potentials of the compounds, and the relevant data are listed in Table . In general, the electron‐donor strength of the chromophores can be evaluated based on their oxidation potential . Therefore, to understand the effect of heteroatoms in the donor units based on their donor strength, the oxidation potentials of the donors were recorded.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…The Fc/Fc + redox couple was used as an internal standard to calibrate the oxidation potentials of the compounds, and the relevant data are listed in Table . In general, the electron‐donor strength of the chromophores can be evaluated based on their oxidation potential . Therefore, to understand the effect of heteroatoms in the donor units based on their donor strength, the oxidation potentials of the donors were recorded.…”
Section: Resultsmentioning
confidence: 99%
“…Similarly, Adachi et al. reported a series of carbazole donors with methyl substituents on peripheral nuclear positions to develop efficient deep‐blue TADF emitters . They demonstrated that the ionization potentials of the donors have a profound impact on control of the Δ E ST value and TADF mechanism of the materials, which obviously dominated the performance of their devices.…”
Section: Introductionmentioning
confidence: 97%
See 2 more Smart Citations
“…TADF emitters can harvest triplet excitons through an efficient up‐conversion process by reverse intersystem crossing (RISC) from the triplet excited state (T 1 ) to the singlet excited state (S 1 ) . TADF materials should have a sufficiently small energy gap between S 1 and T 1 (Δ E S−T ) for the RISC process, which is achieved by tuning the highest occupied molecular orbital (HOMO)–lowest unoccupied molecular orbital (LUMO) separation …”
Section: Introductionmentioning
confidence: 99%